2009
DOI: 10.1152/ajpcell.00117.2009
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-specific aquaporin 12 null mice showed increased susceptibility to caerulein-induced acute pancreatitis

Abstract: Aquaporin 12 (AQP12) is the most recently identified member of the mammalian AQP family and is specifically expressed in pancreatic acinar cells. In vitro expression studies have revealed that AQP12 is localized at intracellular sites. To determine the physiological roles of AQP12 in the pancreas, we generated knockout mice for this gene (AQP12-KO). No obvious differences were observed under normal conditions between wild-type (WT) and AQP12-KO mice in terms of growth, blood chemistry, pancreatic fluid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Decreased expression for at least 66% of these genes is due to direct PTF1A control (asterisks). For example, AQP12 is the intracellular water pump that concentrates secretory proteins during passage to and within zymogen granules (44). Its mRNA decreased to 24% by 6 days, and PTF1A and RBPJL bind a control region occupied by RNAPII and methylated H3K4 near its transcriptional start site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased expression for at least 66% of these genes is due to direct PTF1A control (asterisks). For example, AQP12 is the intracellular water pump that concentrates secretory proteins during passage to and within zymogen granules (44). Its mRNA decreased to 24% by 6 days, and PTF1A and RBPJL bind a control region occupied by RNAPII and methylated H3K4 near its transcriptional start site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The data sets for three control mice and three Ptf1a-cKO mice 14 days after the beginning of tamoxifen treatment have been reported previously (GEO accession number GSE70542) (23). The RNA-Seq data sets for five 6-day TAM-treated control mice (40,42,34,33, and 31 million aligned reads) and three 6-day TAM-treated Ptf1a-cKO mice (41,44, and 49 million aligned reads) for this study were acquired in the same manner (GEO accession number GSE86261).…”
Section: Mice the Generation Of The Mouse Lines With The Genotypes Pmentioning
confidence: 99%
“…To obtain the ER from the mouse kidneys, an ER extraction kit (Imgenex, San Diego, CA) was used following the manufacturer's instructions as previously reported. 41 …”
Section: Isolation Of Er From the Kidneymentioning
confidence: 99%
“…An intriguing observation has been made by Ohta et al (86) who found AQP12 expressed in the rough endoplasmic reticulum (rER) of rat pancreatic acinar cells. In CCK-8 treated rats, AQP12 was present in the rER and also on the membranes of ZGs near the rER.…”
Section: Channels H 2 O Channelsmentioning
confidence: 97%
“…In CCK-8 treated rats, AQP12 was present in the rER and also on the membranes of ZGs near the rER. Furthermore, AQP12 knockout mice were more prone to caerulein-induced pancreatitis (86). The authors suggested that AQP12 may be involved in the mechanisms underlying the proper generation, maturation and trafficking of ZGs in the secretory pathway and that adequate H 2 O flux may be necessary for this process to function adequately.…”
Section: Channels H 2 O Channelsmentioning
confidence: 99%